Phosphorus supplementation does not affect the intake, digestibility, and meat quality of Nellore young bulls fed with high-grain diets - Lima, Laís De Oliveira [UNESP]; Souza, Vinícius Carneiro De [UNESP]; Messana, Juliana Duarte [UNESP]; Castagnino, Pablo De Souza [UNESP]; Lima, Ana Rebeca Castro [UNESP]; Berchielli, Telma Teresinha [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2020)
This study evaluated the effect of phosphorus (P) supplementation on the intake, digestibility, and quality of aged meat from Nellore young bulls fed on high-grain diets finished in feedlot. Forty young bulls (30 months old) with an initial body weight (IBW) of 296 ± 25 kg were used. It was distributed in a completely randomized experimental design. The treatments were: without P supplementation (CO), commercial mineral supplement (CM), and supplementation with dicalcium phosphate (DP) with 2.4, 4.2, or 5.0 g of P per kg of dry matter (DM), respectively. Diets were composed of sugarcane bagasse (200 g kg-1) plus concentrate (800 g kg-1) on a dry matter (DM) basis. The meat quality parameters analyzed were pH, color, cooking losses, shear force, and water-holding capacity. P supplementation did not affect the intake and digestibility of nutrients There was no interaction (p > 0.05%) between diets and the aging time for the meat quality parameters. However, bulls fed with DP exhibited lower pH (5.98) compared to CO and CM (6.19 and 6.14, respectively). The longer aging time increased the cooking losses and intensity of yellow (b*). Under Brazilian conditions, feedlot Nellore cattle fed with high-grain diets do not require additional mineral supplements.
Keywords: cattle; feedlot; mineral; supplement